Is Betula carpatica genetically distinctive? A morphometric, cytometric and molecular study of birches in the Bohemian Massif with a focus on Carpathian birch - Kuneš, Ivan; Linda, Rostislav; Fér, Tomáš; Karlík, Petr; Baláš, Martin; Ešnerová, Jana; Vítámvás, Jan; Bílý, Jan; Urfus, Tomáš (PLoS One, 2019)
Until recently, Czech taxonomists often treated Betula carpatica as a distinct species. Several morphological traits for distinguishing B. carpatica from B. pubescens or other birches are described in literature; however, it has been proven impossible to reliably identify B. carpatica in the field. With the use of morphological and molecular approaches, we intended to assess the position of B. carpatica in the context of other birch taxa reported from the Bohemian Massif and to find more reliable morphological traits for their identification. In our dataset, we distinguished the following birch taxa referred to in the recent Czech literature: B. pendula, B. pubescens, B. carpatica, B. oycoviensis, B. nana, B. petraea and B. ×seideliana. We complemented them with triploids and several diploid and tetraploid "working units" into which we included intermediate individuals that in terms of morphology did not unambiguously match any of the abovementioned birch taxa. Holoploid genome size was measured to determine the ploidy level. To identify genetic relationships between selected taxa and "working units", microsatellite analyses were performed. Model-based STRUCTURE analysis together with principal coordinates analysis (PCoA) based on genetic distances was performed to identify the similarities in multilocus genotype data between groups distinguished in the dataset. The applied analyses were not able clearly to distinguish any group among tetraploid individuals. In this light, it was of no use to search for any more reliable morphological traits of B. carpatica and also B. petraea. Among diploids, B. nana was always distinguished, in contrast to B. oycoviensis, which was not genetically recognized despite being usually morphologically distinct. Based on our results and a literature review, we suggest that B. carpatica and also the closely similar B. petraea should not be considered separate species. A similar conclusion seems relevant also for B. oycoviensis; however, further verification is desirable in this case.
Keywords: Diploidy; Česká republika; Tetraploidy; Ploidies; bříza; diploidie; Genotype; Betula; genotyp; Betulaceae; ploidie; tetraploidie; Czech Republic; břízovité